2021
DOI: 10.33394/j-ps.v9i2.4150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Low Student Achievement in Fifth Grade of Elementary School

Abstract: This study aimed to determine the internal and external factors that cause low learning achievement of fifth-grade students at SDN 1 Barejulat. Internal factors include intelligence, interests, talents, and motivation, while external factors include family, school, and community. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, observations, and documentation studies.  Instrument using interview sheet. The data analysis technique u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
1
1
0
1
Order By: Relevance
“…In addition, talent also affects learning achievement. This conclusion is similar to that stated by Dilvina, Witono, and Safruddin, who stated that those who got low learning scores were caused by a lack of interest and talent (Dilvina, Witono, & Safruddin, 2021). Another dominant factor from the analysis results is the lecturer variable on external factors.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, talent also affects learning achievement. This conclusion is similar to that stated by Dilvina, Witono, and Safruddin, who stated that those who got low learning scores were caused by a lack of interest and talent (Dilvina, Witono, & Safruddin, 2021). Another dominant factor from the analysis results is the lecturer variable on external factors.…”
Section: Discussionsupporting
confidence: 88%
“…Experiential learning research and found that the effect of experiential learning on the form of teamwork was very significant (Jose et al, 2017;Nugroho, 2017). This is supported by the four stages of the experiential learning cycle, Research conducted by Kolb in, who defines "knowledge" as a transformation process that is created and remade continuously (Dilvina et al, 2021;Puspitowati, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Bagi siswa, motivasi belajar dapat membangun semangat belajar yang akan memotivasi mereka untuk terlibat dalam proses pembelajaran (Meşe et al, 2021). Siswa senang mengikuti kegiatan pendidikan karena mereka terinspirasi untuk belajar dengan baik untuk masa depan (Dilvina et al, 2021). Motivasi belajar memberikan prioritas pada reaksi kognitif, yaitu, kecenderungan siswa untuk menyelesaikan tugas-tugas akademik yang berharga dan berusaha untuk mendapatkan keuntungan darinya (Batubara et al, 2020).…”
Section: Pendahuluanunclassified